2016
DOI: 10.1089/jpm.2015.0234
|View full text |Cite
|
Sign up to set email alerts
|

Making the Case for Palliative Care at the System Level: Outcomes Data

Abstract: Early involvement of PC services emerged as advantageous to the net benefit. Given that health care's changing landscape will increasingly include bundled payment and risk holding strategies to improve quality and reduce cost in health care systems, systemwide PC will play a vital role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…In this large, nationally representative database analysis, inpatient PC visit during hospital admission for HF was associated with decreased 9‐month readmission rates. This is consistent with existing literature demonstrating decreased readmission rates in patients receiving inpatient PC involvement . The large number of patients readmitted for HF is consistent with data from a recent large database‐driven study from Dharamajan et al ., who found that 35.2% of 30‐day readmissions following a HF hospitalization were for the same diagnosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this large, nationally representative database analysis, inpatient PC visit during hospital admission for HF was associated with decreased 9‐month readmission rates. This is consistent with existing literature demonstrating decreased readmission rates in patients receiving inpatient PC involvement . The large number of patients readmitted for HF is consistent with data from a recent large database‐driven study from Dharamajan et al ., who found that 35.2% of 30‐day readmissions following a HF hospitalization were for the same diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…Inpatient PC consultation has been shown to decrease 30-day readmission rates in mixed patient populations [20][21][22][23]. However, two recent single-centre studies have not upheld this relationship in the HF population, and there remains clinical equipoise this area [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies have varied in their methodology and approach, there has been a general trend toward specialized palliative care consultation being associated with better outcomes, with improvements in survival, documen-tation of advance directives, and quality of life, as well as decreases in intensive care unit (ICU) admission, ICU length of stay, and the use of nonbeneficial life-sustaining therapies. [1][2][3][4][5] It seems that within single centers, it is possible to deliver specialized palliative care to affect the intended outcomes of improving quality of life and decreasing unnecessary treatment intensity; whether these benefits have translated outside of single-center settings is unknown. However, the ability to perform larger multicenter studies using administrative data to examine this question has been limited by the absence of accurate, efficient ways to identify patients who receive a palliative care consultation.…”
Section: Introductionmentioning
confidence: 99%
“…(2016) had a majority of Black patients within the study. Two studies focused on patients with HF (Chuang, Kim, Blank, Southern & Fausto, 2017;Wiskar, Celi, Walley, Fruhstorfer, & Rush, 2017), two studies had the majority of patients with septicemia (Bharadwaj, et al, 2016;Zalenski, et al, 2016), two studies focused on oncology patients Zhang, et al, 2017), the other studies did not have a specific patient population identified, but used a trigger for a PC consult (Gagne Henderson et al, 2017;Lathrop, & Gottfried, 2015).…”
Section: Study Characteristics and Participantsmentioning
confidence: 99%
“…The tasks and role of PC practitioners in practice varies substantially. Recent research has addressed inpatient and outpatient PC programs in non-academic center hospitals and the benefits of implementation of PC consultation earlier in care of chronic illnesses outside of oncology (Bharadwaj, et al, 2016;Hughes & Smith, 2014;Meier, 2011;Provinciali et al, 2016).…”
Section: Introductionmentioning
confidence: 99%